The effectiveness of local wisdom-based interactive digital module on students’ critical thinking disposition - Syahfitri, Jayanti; Muntahanah, Muntahanah (Institute of Advanced Engineering and Science, 2024)
Local wisdom-based interactive digital module are alternative teaching materials to facilitate meaningful learning and experience, to stimulate the use of thinking skills including critical thinking dispositions. This study applied quasi-experimental design with pretest and posttest control group. Respondents involved in this study were 109 students from senior high school in Bengkulu, Indonesia. The class selection was carried out randomly to determine the interactive digital module class (X1), the e-module class (X2), and the control class (K). Students’ critical thinking dispositions were measured through the Critical Thinking Disposition in Biology Test (CTDBT) instrument which included 10 questions for each of the seven disposition indicators. The data were analyzed using the Kolmogorov-Smirnov test, Levene test, one-way ANOVA test, and LSD. After the data were known to be normally distributed and homogeneous, an ANOVA test was carried out with the result that there was a significant difference in the experimental class and the control class on students’ critical thinking disposition scores, namely 0.008<0.05. This showed that interactive module improve students’ critical thinking dispositions, compared to e-module and control classes. The critical thinking disposition which increased significantly was shown in the truth-seeking indicator. However, the e-module class did not differ significantly from the control class in improving students’ critical thinking dispositions. Therefore, teachers can use local wisdom-based interactive digital module in biology learning.